2008
DOI: 10.1007/s00125-008-1116-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of type 2 diabetes: tracing the reverse route from cure to cause

Abstract: The metabolic abnormalities of type 2 diabetes can be reversed reproducibly by bariatric surgery. By quantifying the major pathophysiological abnormalities in insulin secretion and insulin action after surgery, the sequence of events leading to restoration of normal metabolism can be defined. Liver fat levels fall within days and normal hepatic insulin sensitivity is restored. Simultaneously, plasma glucose levels return towards normal. Insulin sensitivity of muscle remains abnormal, at least over the weeks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
218
3
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(238 citation statements)
references
References 48 publications
10
218
3
7
Order By: Relevance
“…Whether IR leads to hepatic steatosis or whether fat accumulation in the liver is the primary event leading to hepatic and consequently peripheral IR is not entirely clear (7). It has been proposed that a fatty liver and hepatic IR are key factors in and initiators of a twin vicious cycle underlying the pathophysiology of type 2 diabetes (29). NAFLD, as manifested by elevated ALT levels, predicts the future development of diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Whether IR leads to hepatic steatosis or whether fat accumulation in the liver is the primary event leading to hepatic and consequently peripheral IR is not entirely clear (7). It has been proposed that a fatty liver and hepatic IR are key factors in and initiators of a twin vicious cycle underlying the pathophysiology of type 2 diabetes (29). NAFLD, as manifested by elevated ALT levels, predicts the future development of diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the beta-cells to excess fatty acids derived from circulating and locally deposited triacylglycerol suppresses glucose-mediated insulin secretion. 11 This decline in beta-cell function starts several years before the diagnosis of T2D; the Whitehall II study demonstrated gradually increasing fasting plasma glucose (FPG) levels for 10-12 years prior to diagnosis of T2D. 12 This trajectory changes dramatically two years before diagnosis, reflecting acute beta-cell decompensation ( Figure 1).…”
Section: Current Diabetes Management and Challengesmentioning
confidence: 99%
“…The associated time course of decrease in liver volume is over days [10]. Conversely, the period before onset of Type 2 diabetes is characterized by accumulation of liver fat [11].…”
Section: Referencesmentioning
confidence: 99%